2020
DOI: 10.1002/uog.22072
|View full text |Cite
|
Sign up to set email alerts
|

COngenital heart disease and the Diagnostic yield with Exome sequencing (CODE) study: prospective cohort study and systematic review

Abstract: What are the novel findings of this work? This is the first systematic review assessing the incremental yield of antenatal exome sequencing over chromosomal microarray analysis or karyotyping in prenatally diagnosed congenital heart disease. The results show an apparent incremental yield of exome sequencing in these cases. What are the clinical implications of this work? Depending on the presence of robust pathways, exome sequencing may be considered in prenatally diagnosed congenital heart disease, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 45 publications
(156 reference statements)
2
46
1
Order By: Relevance
“…This may have underestimated the prevalence of chromosomal aberrations as exome sequencing (ES) was not performed. A recent study and meta‐analysis by Mone et al found a diagnostic yield of ES in isolated CHD was 11.5%, 20 however, whether this applies to isolated VSDs, in particular, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This may have underestimated the prevalence of chromosomal aberrations as exome sequencing (ES) was not performed. A recent study and meta‐analysis by Mone et al found a diagnostic yield of ES in isolated CHD was 11.5%, 20 however, whether this applies to isolated VSDs, in particular, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed in UK fetal medicine centers identified that the diagnostic yield of prenatally diagnosed CHD using quantitative fluorescence-PCR (QF-PCR), chromosome microarray (CMA), and exome sequencing (ES) was 15.6%, 13.7%, and 10.2%, respectively [ 31 ]. Another recent study concluded that most CHD diagnoses using prenatal ES are associated with extracardiac anomalies rather than isolated cardiac abnormalities [ 32 ]. Therefore, genetic testing has a low yield for sporadic CHD but should be used in patients with familial and syndromic CHD, despite the existence of a significant proportion of incidental findings and variants of unknown significance.…”
Section: Genetic Basismentioning
confidence: 99%
“…The most solid predictions can be made for CHD, with an 8%-13% diagnostic yield consistent among vast cohorts ranging from 197 to 610 samples [ 37 , 38 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%